Mutation in the myelin proteolipid protein gene alters BK and SK channel function in the caudal medulla - Mayer, Catherine A. (2009)
Proteolipid protein (Plp) gene mutation in rodents causes severe CNS dysmyelination, early death, and lethal hypoxic ventilatory depression (Miller et al. 2004). To determine if Plp mutation alters neuronal function critical for control of breathing, the nucleus tractus solitarii (nTS) of four rodent strains were studied: myelin deficient rats (MD), myelin synthesis deficient (Plp(msd)), and Plp(null) mice, as well as shiverer (Mbp(shi)) mice, a myelin basic protein mutant. Current-voltage relationships were analyzed using whole-cell patch-clamp in 300μm brainstem slices. Voltage steps were applied, and inward and outward currents quantified. MD, Plp(msd), and Plp(null), but not Mbp(shi) neurons exhibited reduced outward current in nTS at P21. Apamin blockade of SK calcium-dependent currents and iberiotoxin blockade of BK calcium-dependent currents in the P21 MD rat demonstrated reduced outward current due to dysfunction of these channels. These results provide evidence that Plp mutation specifically alters neuronal excitability through calcium-dependent potassium channels in nTS.